Radiation-Induced Sarcoma Originating in Recurrent Juvenile Nasopharyngeal Angiofibroma - Smriti Panda; Madhu Rajeshwari; Chirom Amit Singh; Suresh C. Sharma; Pirabu Sakthivel (Case Reports in Oncological Medicine)
Juvenile nasopharyngeal angiofibroma is a benign disease affecting young males with a propensity to invade intracranially and into the orbit along preformed pathways. Complete surgical excision is the mainstay of management. Patients with multiple recurrences along with tumour extension into skull base and orbit can be considered for external beam radiation as either adjuvant or definitive treatment. Possibility of radiation-induced malignancy has been speculated by many authors, proof of which exists in only two studies so far. This report focuses on radiation-induced leiomyosarcoma in a patient with recurrent juvenile nasopharyngeal angiofibroma.